Prevalence of pneumoconiosis among young adults aged 24‐44 years in a heavily industrialized province of China. Issue 1 (21st January 2019) - Zhao, Jun‐Qin; Li, Jian‐Guo; Zhao, Chun‐Xiang
Abstract: Objectives: The purposes of this study were to clarify (i) the prevalence of pneumoconiosis among young adults and (ii) the factors associated with pneumoconiosis among young adults to explore targeted solution for control of pneumoconiosis among young adults (aged 24‐44 years). Methods: The new cases diagnosed from 2001 to 2015 (extracted from the National Occupational Disease and Occupational Health Information Monitoring System) were involved in this research, including information of employer, patient's name, date of birth, gender, date of diagnosis, first year of dust exposure, duration of exposure, aggregation etc Results: A total of 1519 pneumoconiosis cases were diagnosed among young adults (21.6% of overall cases). Silicosis was the most common type with acute process of disease. Compared with overall cases, the young patients had shorter duration of exposure, more stage II/III cases and higher aggravation rate; and were even more concentrated in small and medium enterprises where more migrant workers were employed and insufficient protective measures were used. Without further regulation, the prevalence of pneumoconiosis among young adults would bring not only disease suffering for 3000 individuals and their families, but also an annual economic loss up to 180 million yuan for Hebei province till 2025. Conclusions: As a typical heavily industrialized province of China, Hebei has severe situation on pneumoconiosis among young adults. Special attention and effort on silica‐contacting industries, small and medium enterprises, and migrant workers should be focused in future occupational supervision and regulation among young adults.